PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan Mitrho Egg Quail Boyolali) - Kistiani Hegy Suryana, Alean; Thaharani, Anisa; Ria Safitri, Unna; Sri Anggorowati, Luki (Universitas Boyolali, 2024)
The research aims to determine the effect of leadership style, compensation, and workload partially and simultaneously on employee performance at Mitrho Egg Quail Boyolali. The population of this study amounted to 56 people. Determination of the sample using saturated sampling, because the existing population is used as a research sample. Data collection techniques were carried out through questionnaires, interviews, and observation. Data analysis techniques used quantitative techniques using validity, reliability, normality, heteroscedasticity, autocorrelation, multicollinearity, multiple linear analysis, t-test, and f-test. Research results: 1) Testing states that leadership style has no effect on employee performance, then Ho is accepted and Ha is rejected, this is evidenced by the sig value of 0.061 > 0.05. 2) The test states that compensation has no effect on employee performance, then Ho is accepted, Ha is rejected, this is evidenced by the sig value of 0.498 > 0.05. 3) Testing states that workload has a significant effect on employee performance, then Ho is rejected Ha is accepted, this is evidenced by a sig value of 0.000 <0.05. 4) The test states that leadership style, compensation, and workload simultaneously have a significant effect on employee performance, then Ho is rejected, Ha is accepted, this is evidenced by a sig value of 0.000 <0.05.